Ngengkun Method for Children of Farming Families in Gayo Lues Culture - Dahlia; Sehat Ihsan Shadiqin; Hardiyansyah A.S.Th. I (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2021)
Ngengkun comes from the Gayo language which means parenting. Children are entrusted by God to parents to be educated and guarded so that they grow and develop into good children, parents are leaders in the household for their children to educate their children. However, in caring for children, problems often occur due to the lack of economy and knowledge of both parents, which results in a lack of guidance and guidance, causing children to be disobedient and unmotivated in education. The formulation of the problem in this study is how the parenting pattern in Tengkereng Hamlet and how the efforts of parents in Tengkereng Hamlet in parenting children. This research uses a qualitative method with a descriptive approach that describes accurate phenomena about the facts found in the field. The data obtained in this study are based on the results of in-depth interviews with research respondents, observation, and documentation. The results showed that parents in Tengkereng used primitive and authoritarian parenting.